Indeno[1, 2-b]fluorene-based novel donor–acceptor conjugated copolymers: Electron acceptor engineering and polymer backbone planarization. (March 2018) - Sun, Ying; Ding, Xiaojing; Zhang, Xueqin; Huang, Qizan; Lin, Baoping; Yang, Hong; Guo, Lingxiang
A series of conjugated copolymers based on indeno[1, 2-b]fluorene as donor unit with different acceptor units have been synthesized to explore the influences of molecular backbone planarization and acceptor electronegativity on charge transport and photovoltaic properties. Polymer incorporating 2, 3-diphenylquinoxaline acceptor moiety shows poor light-harvesting capacity and inferior photovoltaic efficiency of 0.5% due to twisted geometry. By introducing the stronger acceptor thiadiazolo[3, 4-c]pyridine in polymer, intramolecular charge transfer is enhanced, giving rise to improved absorption property and photovoltaic efficiency of 1.39%. However, the polymer backbone is still twisted. When thiophene-flanked diketopyrrolopyrrole (DPP) is incorporated as electron acceptor, the polymer exhibits a more planar molecular geometry, yielding a broader and red-shifted absorption spectrum as well as a significantly improved hole mobility of 1.46E-2 cm 2 V −1 s −1 . However, the photovoltaic device efficiency is only enhanced to be 1.69%. The low-lying lowest unoccupied molecular orbital of −3.95 eV as a result of the strong electron deficiency of the DPP unit may lead to the inefficient charge dissociation and increase the charge recombination, which may give rise to the limit photovoltaic performance.